Reduced Chemical Fertilizer Combined With Bio-Organic Fertilizer Affects the Soil Microbial Community and Yield and Quality of Lettuce - Jin, Ning; Jin, Li; Wang, Shuya; Li, Jinwu; Liu, Fanhong; Liu, Zeci; Luo, Shilie; Wu, Yue; Lyu, Jian; Yu, Jihua (Frontiers in Microbiology, 2022)
Reducing chemical fertilizers in combination with bio-organic fertilizers can limit the use of chemical fertilizers while maintaining soil fertility. However, the effects of combined fertilization on soil chemical properties, microbial community structure, and crop yield and quality are unknown. Using high-throughput sequencing, we conducted field experiments using lettuce plants subjected to five fertilization treatments: chemical fertilizer with conventional fertilization rate (CK), chemical fertilizer reduction by 30% + 6,000 kg ha–1 bio-organic fertilizer (T1), chemical fertilizer reduction by 30% + 9,000 kg ha–1 bio-organic fertilizer (T2), chemical fertilizer reduction by 40% + 6,000 kg ha–1 bio-organic fertilizer (T3), and chemical fertilizer reduction by 40% + 9,000 kg ha–1 bio-organic fertilizer (T4). Compared with CK, the T1–T4 had significantly higher soil pH and soil organic matter (SOM) and showed increased richness and diversity of the bacterial community, and decreased richness and diversity of the fungal community. Principal coordinate analysis evidenced that the bacterial and fungal communities of CK and T1–T4 were distinctly separated. The Kruskal-Wallis H-test demonstrated that the fungal community was more sensitive than the bacterial community to chemical fertilizer reduction combined with bio-organic fertilizer. Among the soil chemical parameters measured, only TN (total nitrogen) was significantly correlated with bacterial and fungal community composition. The T1 and T2 increased lettuce yield. Moreover, T1–T4 characterized reduced nitrate content and increased levels of soluble sugars and vitamin C in lettuce. Overall, the combined application of reduced chemical fertilizer and bio-organic fertilizer effectively improved soil fertility, microbial community structure, and lettuce yield and quality. These findings have valuable implications for vegetable safety and long-term environmental sustainability.